New species and records of coelidiine leafhoppers (Hemiptera: Auchenorrhyncha: Cicadellidae) from Brazil - Barbosa, Julianna Freires; Takiya, Daniela Maeda (Zootaxa, 2017)
Three new coelidiine species from Brazil are described: Paraterulia sakakibarai sp. nov. (from Amazonas State), Stalolidia amazonensis sp. nov. (from Amazonas State), and Youngolidia brasiliensis sp. nov. (from Minas Gerais State). The last species represents the first record of Youngolidia Nielson, 1983 in Brazil. In addition, Sandersellus delongi Nielson, 1975 (Sandersellini), Docalidia gracilis Nielson, 1979, Cochanga spinosa Nielson, 1979, Perulidia pilosa Nielson, 1979, Stalolidia setacea Nielson, 2011 (Teruliini), Pilosana bifurcata Nielson, 1983, and Pilosana panna Nielson, 1983 (Youngolidiini) are newly recorded from Brazil. Finally, first records for the following three species from Amazonas State (Brazil) are also provided: Paraterulia magna (Baker, 1898), Stalolidia clava Nielson, 2011 (Teruliini), and Pilosana stylata Nielson, 1992 (Youngolidiini).